FDI, INFLATION, EXCHANGE RATE AND GROWTH IN GHANA: EVIDENCE FROM CAUSALITY AND COINTEGRATED ANALYSIS - Amoah, Emmanuel; Nyarko, Eric; Asare, Kwabena (European Scientific Journal, ESJ, 2015)
This study used co-integrated analysis and Granger causality test in modelling the Growth Domestics Products (GDP) of Ghana with other three selected macroeconomic such as Foreign Direct Investment (FDI), inflation and real exchange rate for the period of 1980 to 2013. Data were taken from the World Bank’s World Development Indicators and Bank of Ghana. The objectives of the study are to examine both long-run relationships and direction of causality between the GDP and the macroeconomic variables. The time series properties of the data were, first, analysed using the Augmented Dickey-Fuller (ADF) test and KPSS test. The empirical results derived indicate that all the variables were stationary after their first differencing; i.e. variables are integrated of order one. The study further established that there is co-integration between the selected macroeconomic variables and GDP in Ghana indicating long run relationship. The above long term relation indicates that exchange rate and foreign direct investments have a negative effect on GDP whiles Inflation (CPI) showed a positive effect on GDP. The study further investigated the causal relationship using the Granger Causality analysis, which indicates a unidirectional causality between GDP growth rate and exchange rate and bidirectional causality between Inflation rate and Exchange, and also between Inflation rate and GDP, whiles FDI does not granger cause Inflation rate, exchange rate, GDP and visa versa in Ghana for the study period at 5%.